The Relationship Between Students Engagement, Creativity, and Fractions Understanding through the Use of Manipulative Materials in Elementary School - Kristin Rainane; Yoppy Wahyu Purnomo; Anwar Novianto; Nurtanio Agus Purwanto; Resky Nuralisa Gunawan (Indonesian Journal of Instruction, 2026)
Education fundamentally aims to develop students’ potential optimally; however, in practice, mathematics learning still faces challenges, particularly low student engagement due to the abstract nature of the material, especially in fraction concepts. This study aims to analyze the effect of using manipulative media on students’ activeness, creativity, and understanding of fraction concepts at the elementary school level. The study employed a quantitative approach with a descriptive correlational method. The participants consisted of a group of students selected through purposive sampling. Data were collected using a closed-ended questionnaire based on a Likert scale, covering the variables of activeness, creativity, and conceptual understanding. The data were analyzed using descriptive statistics to describe learning tendencies, as well as Spearman correlation analysis to examine relationships among variables. The results indicate that the use of manipulative media has a positive and significant effect on improving students’ activeness, creativity, and conceptual understanding. In addition, the relationships among variables show positive correlations with strengths ranging from moderate to very strong. The findings suggest that manipulative media are effective in enhancing active participation, fostering creative thinking, and strengthening students’ understanding of fraction concepts. The implications of this study highlight the importance of integrating manipulative media into mathematics instruction to improve the quality of both the learning process and outcomes at the elementary level.